Validação em métodos cromatográficos para análises de pequenas moléculas em matrizes biológicas Chromatographic methods validation for analysis of small molecules in biological matrices - Neila Maria Cassiano; Juliana Cristina Barreiro; Lúcia Regina Rocha Martins; Regina Vincenzi Oliveira; Quezia Bezerra Cass (Química Nova, 2009)
Chromatographic methods are commonly used for analysis of small molecules in different biological matrices. An important step to be considered upon a bioanalytical method's development is the capacity to yield reliable and reproducible results. This review discusses validation procedures adopted by different governmental agencies, such as Food and Drug Administration (USA), European Union (EU) and Agência Nacional de Vigilância Sanitária (BR) for quantification of small molecules by bioanalytical chromatographic methods. The main parameters addressed in this review are: selectivity, linearity, precision, accuracy, quantification and detection limits, recovery, dilution integrity, stability and robustness. Also, the acceptance criterions are clearly specified.